Harmony Between Humanity and Nature: Natural Vs. Synthetic Drug Preference in Chinese Atheists and Taoists - Cao, Yu (Journal of religion and health, 2022)
A commonplace observation across many cultures is that humans show a strong preference for natural items on drug choice in the medical domain. Despite an emerging line of psychological research on individual differences in the naturalness-is-better bias, few studies have focused on the role of religious beliefs. According to the core idea of Taoism, people should free themselves from selfishness and desire and behave in concert with the alternating cycles of Nature. Based on the findings regarding the positive relationship between connectedness to nature and naturalness preference, we predict that Taoists, who emphasize harmony between humanity and nature, should show a stronger naturalness-is-better bias than atheists on drug choice due to their higher level of natural connectedness. The results showed that both Chinese atheists and Taoists selected a natural over synthetic drug even though the safety and efficacy of the medicines were described as identical. More importantly, the naturalness-is-better bias is more pronounced in Taoists than atheists. These data suggest that religious beliefs related to individuals’ connectedness to nature may moderate the naturalness-is-better bias in health decisions.